Women in science and technology confronting inequalities - Gupta, Namrata (SAGE Publications India Pvt Ltd, 2020)
"Women in Science and Technology: Confronting Inequalities comprehensively explores women's status in the Science and Technology (S&T) domain by rigorously analysing and interpreting extensive recent information on major areas such as engineering, medicine, physical sciences, biosciences and mathematics. The book forcefully demonstrates that gender-based differences and expectations play the determining role in limiting women's participation in S&T. These exist in various forms, from making subject choices in school and opting for specific disciplines in college to embracing specific career avenues such as scientific research. This book shows how the construction of gendered identities is perpetuated through a masculine culture in the informal environment of elite educational institutes and in major S&T workplaces such as academia and research laboratories, which serve together to exclude women from peer groups and opportunities for advancement. The book makes substantive recommendations for policy measures on college admissions, improvement of institutional and organizational environments, and recruitment and capacity building for women in S&T. It calls for substantially reducing the myriad societal and familial barriers through cooperation and understanding."--Provided by publisher.